Hubungan Pengetahuan Ergonomi Terhadap Posisi Kerja Selama Perawatan Kesehatan Gigi Dan Mulut (Penelitian) - Asyurati Asia; Rahayu Putri Andini (Fakultas Kedokteran Gigi Universitas Trisakti, 2020)
Background: Ergonomic is one way to avoid health problems, such as musculoskeletal disorders which occur in 63-93% of dental practitioners. The lack of ergonomic application might arises from the knowledge negligence among dental students.. Purpose: The aim of the study was to study the correlation between ergonomic knowledge and work positions during dental and oral health care by clinical dental student at Dental and Oral Hospital FKG Usakti. Method: This study was an observational analytic using questionnaires containing 20 questions and the European Socienty of Dental Ergonomics (ESDE) form which contains 10 criteria for work position, with a total of 100 respondents. Direct visual examination by the researcher was done first, then respondents were given the questionnaires. Results: Spearman correlation test showed that there was no correlation between ergonomic knowledge with work position during dental and oral health care (p = 0.463). Conclusion: This study showed that there is no correlation between ergonomic knowledge and work positions during dental and oral health care by clinical dental student at the Dental and Oral Hospital of FKG USAKTI.